Homomorphism to R of semidirect products: a dynamical construction - Bettencourt, G. (2016)
We define a modified version of Erschler and Karlsson construction of homomorphisms from random walks [A. Erschler and A. Karlsson, Ann. Inst. Fourier (Grenoble) 60 (2010), no. 6, 2095?2113]. We show that our definition is well adapted to semidirect products. The same construction is conjectured to work also for other classes of maps like quasi-morphisms.